Nature of Multidimensional Poverty Incidence in Rural Nepal: Empirical Evidences from Bhalam VDC, Kaski - Bhattarai, Lekha Nath (Economic Literature, 2016)
This paper attempts to exercise the Oxford Poverty and Human Development Initiative’s methodology to measure the multidimensional poverty at the local (village) level. Various measures of Multidimensional poverty has been estimated and decomposed to the various sub groups of the sampled household of the then Bhalam VDC of the Kaski District, in West Nepal. Stratified random technique was applied to select the 150 sample households to conduct household survey to get required data for the measurement and analysis of poverty. The results of the analysis follows almost similar pattern of various measures of multidimensional poverty estimates of the Oxford latest study. It is also revealed from the study that multidimensional poverty incidence and intensity were highly associated with the household socioeconomic characteristics such as Caste and ethnicity, land holding, gender and educational level of the household head and the family size.Economic Literature Vol.12 2014: 16-25